A rigorous, systematic and integrated methodology to assess viable land use options for mine closure: a case study from Suriname - Stewart, WI; Watt, C; Parshley, JV; Lassiter, P; George, J; Nandlal, A; Van Vlaenderen, H (Mine Closure 2013: Proceedings of the Eighth International Seminar on Mine Closure, 2013)
Suralco L.L.C. (a subsidiary of Alcoa Inc.) is currently preparing an Integrated Closure Plan (ICP) Framework for its landholdings and mining concessions located principally within the Commewijne, Marowijne and Para Districts of Suriname. The purpose of the ICP Framework process is to act as an overarching template that can be followed to determine acceptable land use options and completion criteria for mine closure based on the physical, biophysical and socio-economic conditions of each disturbed mine site. The ICP Framework was built around a concise decision tree logic, permitting a very structured approach. Due to the array of potential post-closure land use options, a key component of the ICP Framework was the identification and assessment of viable and sustainable post-closure land uses. The determination of post-closure land uses is recognised in the literature and by practitioners as an important part of the mine closure planning process. However, it is often undertaken in an ad hoc manner and the process poorly documented. The need for rigorous methodologies is particularly important where clear regulatory criteria defining closure are not readily available. An innovative approach to assessing post-closure land use options in the form of a preliminary land use viability assessment tool (PLUVAT) is detailed that enabled an unprecedented level of integration across all the applicable disciplines and delivered a well-documented result that has responded well to both regulatory and stakeholder scrutiny and that promises to become a preferred model to define acceptable rehabilitation of mined areas in this region. The benefits of this approach to evaluating and documenting post-closure land use options and the high level of integration achieved across the various biophysical, socio-economic and technical disciplines are also explored.